Pengaruh Keefektifan Audit Sistem Informasi, Risiko Keamanan Audit Sistem Informasi, dan Strategi Audit Sistem Informasi terhadap Pendeteksian Salah Saji - Betri Betri; Welly Welly; Ida Zuraidah; Lis Djuniar; Ambo Upek (Universitas Muhammadiyah Palembang, 2025)
This study aims to analyze the influence of information systems audit effectiveness, information systems audit security risk, and information systems audit strategy on the detection of misstatements in Public Accounting Firms in Palembang City. This is an associative research using a quantitative approach. The population consists of 60 auditors, with a saturated sampling technique. Primary data were collected through questionnaires and interviews, and processed using SPSS version 23. The results show that all variables are valid and reliable. Simultaneously, audit effectiveness, security risk, and audit strategy significantly affect misstatement detection. Partially, security risk and audit strategy have a significant influence, while audit effectiveness does not have a significant effect. These findings highlight the importance of audit strategy and security risk management in detecting misstatements in information systems audits within public accounting firms.